Perfil de vitimização da violência doméstica dos municípios da 15ª Regional de Saúde de Maringá - 2012-2014 - Calazans, Cristiane Muller (2016)
Violence is a phenomenon that has been presenting every year an increase in its manifestations, leading to social unrest. The present research was seeking to know the victimization profile of domestic violence at the 15th Health's Regional of Maringa-Pr, through the SINAN database 2012-2014. The research is classified as quantitative. The statistical data processing was initially through the descriptive analysis model, using the SPSS 2.0 software. And to establish the risk profile for manifestation of violence and verify, which of these, has the greatest chance of recurrence, was used the Binary Logistic Regression model. From the analysis it was arrived thourgh the following considerations that indicates the descriptive profile as, women with elementary education, aged from 18-49 years, being the most frequently reported the physical violence, followed by sexual. The risk profile of physical violence, abandonment/ neglect and financial/ economic is the older age group. Then the risk profile of sexual violence being female and in the most defenseless age is from 0 to 12 years. The risk profile for the psychological / moral violence is being woman, married regardless of age. We can consider that in the municipalities that compose the 15th Health's Regional of Maringa, have elderly, married women, children and adolescents, whith are the segments with the higher fragility of risk to the manifestations ofdomestic violence. Regarding the risk profile of the recurrence of manifestations of the domestic violence, have the financial violence / economic, psychological and neglect / abandonment, by order of highest risk. And about the aggressor there is a higher propensity to be male in various manifestations and be alcoholized added the risk of committing violence. Through this research it was possible to envision the possibilities that public policies have to invest their efforts and financial resources.